Web 2.0: A Movement within the Learning Community - Ahmed, Amira Mahmoud (Information Management and Business Review, 2012)
Web 2.0 technologies provide members of the learning community with new and innovative ways to create disseminate and share information both individually and collaboratively. This phenomenon has been termed e-Learning 2.0. However, e-Learning 2.0 is more than the application of these technologies in the learning community; it is a movement that is beginning to transform the nature of learning. In this paper we present and explain four Web 2.0 technologies - blogs, wikis, podcasts, and social networks - and look at how these technologies are currently being used by staff. We consider the use of Web 2.0 technologies by students to find and share information and to form support communities and then we explore a Web 2.0 pedagogical model that would connect students - tomorrow’s professionals - with today’s professionals in order to enhance student education through providing collaborative learning opportunities together with ready access to multiple sources of information and expertise.